2016
DOI: 10.1038/sdata.2016.54
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput ab-initio dilute solute diffusion database

Abstract: We demonstrate automated generation of diffusion databases from high-throughput density functional theory (DFT) calculations. A total of more than 230 dilute solute diffusion systems in Mg, Al, Cu, Ni, Pd, and Pt host lattices have been determined using multi-frequency diffusion models. We apply a correction method for solute diffusion in alloys using experimental and simulated values of host self-diffusivity. We find good agreement with experimental solute diffusion data, obtaining a weighted activation barri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
90
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(93 citation statements)
references
References 29 publications
2
90
0
Order By: Relevance
“…Recently, Nandipati et al also found the distinction between 1b-1b and 1b-1b jump using self-learning kinetic Monte Carlo [64]. As previous computational studies [20][21][22][23] relied on the 8-frequency framework to model diffusion and identify which transition states to compute, these uncontrolled approximations can cause significant quantitative and qualitative errors in transport coefficients.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, Nandipati et al also found the distinction between 1b-1b and 1b-1b jump using self-learning kinetic Monte Carlo [64]. As previous computational studies [20][21][22][23] relied on the 8-frequency framework to model diffusion and identify which transition states to compute, these uncontrolled approximations can cause significant quantitative and qualitative errors in transport coefficients.…”
mentioning
confidence: 99%
“…Transport coefficients are fundamental inputs for models at the length and time scales of microstructure evolution. However, computational modeling of transport coefficients for Mg alloys has used oversimplified models that lead to incorrect predictions, despite using accurate ab initio data as inputs [20][21][22][23].…”
mentioning
confidence: 99%
See 3 more Smart Citations